AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERRORS IN WRITING ENGLISH TEXT IN THE SECOND GRADE STUDENTS OF SMK-SMTI BANDA ACEH - Hijjatul Qamariah; Sri Wahyuni; Meliana (Getsempena English Education Journal, 2020)
Writing has been a challenging skill for EFL or ESL Students to cope with. It needs not only the ability to compose a good piece of writing but also goes on a deep layer called grammatical aspect. Understanding grammar is vital to construct a good sentence. Therefore, this study aims at finding out the types of grammatical errors produced by students while composing the English text. Ten students (10) in the second grade of SMK-SMTI Banda Aceh were selected as participants in this study. They were given a task to compose English texts. Then those 10 students writing sheets were analyzed to find out the grammatical errors made. The results revealed that there were 11 categories of grammatical error types; error in using verb, tense, singular/plural noun, adjectives, preposition, to be, articles, modal/auxiliary, noun, objective pronoun, and phrasal verb with the total of grammatical made are 48 total numbers of errors that students produced in their writing sheet. It can be concluded that these 10 students still cannot compose a good sentence because they still made errors in using the grammatical rule.